Religious Bigotry: A Threat to Ordered State - LIMAYE (Madhu)
Articles, chiefly on communalism in the light of Indian religious perspective.
Keywords: Comparative Religion; Hindus and Muslims in India; Lahore Shahid Ganj; Babri Mosque; Sangh Pariwars War; Communal Parties